2012
DOI: 10.1017/s0950268812000015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative hepatitis A seroepidemiology in 10 European countries

Abstract: SUMMARYThe WHO recommends hepatitis A virus (HAV) immunization according to level of transmission and disease burden. We aimed to identify susceptible age groups by standardized serosurveys to inform HAV vaccination policy in participating countries : Belgium, Czech Republic, England, Finland, Germany, Italy, Lithuania, Malta, Romania, and Slovakia. Each country tested national serum banks (n=1854-6748), collected during 1996-2004, for anti-HAV antibodies. Local laboratory results were standardized to common u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 40 publications
2
32
0
3
Order By: Relevance
“…Younger household contacts had a higher frequency of HAV infection, corroborating recent studies showing an increase in the age at which HAV infection occurs [4], [25], [26]. However, the presence of previous immunity was associated with older (>20 years of age) household contacts; this finding was in accordance with many epidemiological studies reporting a strong association between age and anti-HAV prevalence [5], [26], [27], [28].…”
Section: Discussionsupporting
confidence: 88%
“…Younger household contacts had a higher frequency of HAV infection, corroborating recent studies showing an increase in the age at which HAV infection occurs [4], [25], [26]. However, the presence of previous immunity was associated with older (>20 years of age) household contacts; this finding was in accordance with many epidemiological studies reporting a strong association between age and anti-HAV prevalence [5], [26], [27], [28].…”
Section: Discussionsupporting
confidence: 88%
“…This was an expected finding and concordant with other previous studies carried out in Europe, which reported 70% to 94% susceptibility rate of those aged <30 years. [14] In other hands, this group revealed a lower seroprevalence because people were not target of vaccination program but experimented the effect of the reduction of HAV circulation due to the vaccination program.…”
Section: Discussionmentioning
confidence: 99%
“…High-income countries usually have low or very low HAV incidence rates, and seroprevalence studies typically show an AMPI that is in middle adulthood. For example, in many Western and Northern European countries, the AMPI is above 50 years, which means that more than half of 50-year-olds and the vast majority of children and younger adults remain susceptible to HAV infection (Kurkela et al 2012;Carrillo-Santisteve et al 2017). When a large proportion of hepatitis A cases occur among adolescents and adults, the case detection rate is usually fairly high because nearly all infected individuals in these age groups develop jaundice.…”
Section: Hepatitis a Virus (Hav) Epidemiologymentioning
confidence: 99%